The efficiency comparison of the road management system in oil palm plantation / Mohd Saiful Abdul Wahil - Abdul Wahil, Mohd Saiful (Faculty of Plantation and Agrotechnology, 2016)
Nowadays, the successful of the oil palm plantation nowaday are coming from the company management system. Reducing the cost of operating maintenance will help to increase the profit of the company. There are always some effects if the road system is not managed well. Many unnecessary cost will burden the company to cover for example road repair and tractor maintenance cost. So, this study was done to compare between the different road management systems and determine which are better. The data are collected from Mados's Lenggor and Tradewind Ladang Petri Tenggara, Johor. The data of road repair cost, tractor maintenance cost, no of collected bunches and output yield weight was collected from the year 2015. The result showed that road management system in field will give the impact to the cost and yield production of the oil palm.